Characterization studies on red clover (Trifolium pratense L.) - Celalettin Aygün (Artvin Çoruh Üniversitesi Orman Fakültesi Dergisi, 2015)
A case study in characterizations of red clover (T. pretense L.) some Morphological and physiological characterizations of ecotypes of red clover (T. pretense L.) genotypes were classified as seven groves dendogram a six groups in biplot analysis. Plant height was considered as dependent variable in path analysis showing direct and indirect effect of the other characteristics. Results showed that speed and power of germination leaf length and leaf height, thickness of stalk had significant effect on plant height. Some plant characteristics hawing significant relationship with plant height should be taken into consideration in development of novel genotypes in breeding programs.